Die oberdevonische flora des Ellesmere-Landes (Mit 7 tafeln und 4 figuren im texte) - Nathorst, A. G. (Alfred Gabriel), 1850-1921. (Kristiania, Pub. by Videnskabs-selskabet i Kristiania, Printed by A. W. Brøgger, 1904)
"At the expence [sic] of the Fridtjof Nansen fund for the advancement of science." Mode of access: Internet.